Design and Implementation of Differentiation Strategy and Business to Business (B2B) Parfume Inclosure - Rasyid Agung Prawira; Erlita Ridanasti (Cita konsultindo, 2024)
In Indonesia, perfume entered through trade and cultural interaction during the colonial period by the Dutch and Portuguese, enriching local aromas. The perfume industry is experiencing rapid growth with increasing demand and digitalization. The development of public interest in fragrance is increasing along with public awareness in looking neat and fragrant. Seeing the golden opportunity that exists, Perfume Inclosure is present in the perfume industry as one of the perfume brands among local Indonesian brands. The purpose of this report is to identify a strong differentiation strategy for Inclosure perfume products in an increasingly competitive market and initiate a business model that applies the concept of Business to Business (B2B) for distributors (resellers). The development of the Perfume Inclosure business starts from the production aspect which includes the preparation of raw materials, producing perfume, and monitoring production quality. Marketing aspects that include promotional strategies, distribution channels, and pricing policies. Aspects of the organization/HR include organizational structure, determination of the number of employees, HR work qualifications and the recruitment process. The financial aspect includes the level of cost efficiency such as operational costs, human resource costs and marketing costs. The results of this report show that Perfume Inclosure faces several challenges in increasing sales, so the solution offered is product differentiation to increase market attractiveness and influence purchase decisions, while the B2B concept with resellers increases sales quantity and sustainable sales flow.